SYNTHESIS AND EVALUATION OF ANTIMICROBIAL ACTIVITIES OF SOME NOVEL, N-INDOLYLMETHYL SUBSTITUTED MANNICH BASES OF 5-ARYLIDENYL THIAZOLIDINE-2, 4-DIONE DERIVATIVES. (International Journal of Food and Nutritional Sciences, 2022)
A novel series of 3-((1H-indol-1-yl)methyl)-5-arylidenyl thiazolidine-2,4-diones derivatives (6a-h) were prepared by the Mannich reactions of 5-(substituted arylidene)thiazolidine-2,4-dione (3a-h) derivatives with formaldehyde (4) and Indole (5). Structures of the newly synthesized compounds were assign on the basis of IR, 1HNMR and mass spectral studies. A series of newly synthesized compounds (6a-h) were tested for their in-vitro antibacterial ativities against Gram-positive (B. subtilis) bacteria and Gram-negative (E. coli) bacteria, antifungal activity against pathogenic fungal strains (C. albicans). Some of the compounds exhibited promising antibacterial and antifungal activities.